2016
DOI: 10.3109/15376516.2016.1172284
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of cuprizone a Cu2+chelating agent on isolated mouse brain mitochondria: a justification for demyelination and subsequent behavioral dysfunction

Abstract: Multiple Sclerosis (MS) is a complex disease with an unknown etiology and no effective cure, despite decades of extensive research that led to the development of several partially effective treatments. In this study we aimed to investigate brain mitochondrial dysfunction in demyelination induced by cuprizone in mice. Cuprizone was used for induction of demyelination in mice through a diet containing 0.2% w/w cuprizone for 5 weeks. Behavioral tests for proving of MS was performed and then mitochondria from brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 31 publications
4
41
0
1
Order By: Relevance
“…After incubating isolated heart mitochondria with Li + (0, 75, 125, 250, and 500 μM) in respiration buffer containing 0.32 mM sucrose, 10 mM Tris, 20 mM Mops, 50 μM EGTA, 0.5 mM MgCl 2 , 0.1 mM KH 2 PO 4 , and 5 mM sodium succinate, the mitochondrial H 2 O 2 production was assayed by F‐2500 fluorescence spectrophotometer (HITACHI) using DCFH‐DA (final concentration, 10 μM) for a period of 60 min. Excitation and emission wavelengths were 485 and 530 nm, respectively …”
Section: Methodsmentioning
confidence: 99%
“…After incubating isolated heart mitochondria with Li + (0, 75, 125, 250, and 500 μM) in respiration buffer containing 0.32 mM sucrose, 10 mM Tris, 20 mM Mops, 50 μM EGTA, 0.5 mM MgCl 2 , 0.1 mM KH 2 PO 4 , and 5 mM sodium succinate, the mitochondrial H 2 O 2 production was assayed by F‐2500 fluorescence spectrophotometer (HITACHI) using DCFH‐DA (final concentration, 10 μM) for a period of 60 min. Excitation and emission wavelengths were 485 and 530 nm, respectively …”
Section: Methodsmentioning
confidence: 99%
“…However, the mechanism by which cuprizone is thought to unfold its toxicity is via disturbing both mitochondrial functions as well as important detoxifying enzymes such as superoxide dismutase (Faizi et al, 2016). However, the mechanism by which cuprizone is thought to unfold its toxicity is via disturbing both mitochondrial functions as well as important detoxifying enzymes such as superoxide dismutase (Faizi et al, 2016).…”
Section: Relevance Of the Cuprizone Model For Studying Nrf2-signalingmentioning
confidence: 99%
“…What activates the UPR in cuprizone‐intoxicated mice? It is suggested that the Cu 2+ chelating agent cuprizone causes mitochondria dysfunction leading to decreased ATP production and increased reactive oxygen species (ROS) formation (Faizi et al, ). In support of this assumption, we recently demonstrated that cuprizone induces the activation of the nuclear factor erythroid 2‐related factor 2 (Nrf2) pathways, which is the main transcriptional regulator of the anti‐oxidant stress defense (Draheim et al, ).…”
Section: Discussionmentioning
confidence: 99%